Pengaruh Knowledge Management terhadap Performa Kinerja Organisasi: Studi Kasus pada PT Ericsson Indonesia - Stephanus Stephanus (Bina Nusantara University, 2012)
Human resources are the most important asset as the primary determinant of long-term corporate success. Therefore, any efforts to improve the effectiveness and performance of employees in a company or organization are also important factors in improving the the company's capacity of available Intellectual Capital. In addition, learning environment holds important implications for improving organizational performance in a company, especially when associated with knowledge Management that can be used as a learning enabler undertaken by their employees. This paper discusses the relationships between the learning environment and the increase of organizational performance associated with the company’s knowledge management.